Edurail: Railway Simulation Using Virtual Reality Technology - ABDUL RASID, NABIL NUR HAKIMI; Norhalina Senan (Applied Information Technology And Computer Science, 2026)
Virtual reality is new, advanced technology that has created digital environments that allow users to interact with virtual scenarios in the most realistic and intuitive manner. In railway education and similar fields, several related VR applications are useful. Some of the simulation programs are really trying to improve learning with a better sense of interaction, but some simulators are more game-oriented than educationally oriented. Some do not adequately transfer the knowledge and skills during the training process. In addition, railway training in Malaysia is still conducted within a classroom setting, which creates the gulf between theory and practice, undermining the preparedness of the students for real life situations and possibly leading to dangerous situations in railway operations. EduRail: Railway Simulation is proposed to solve these problems. EduRail utilizes VR technology in bridging theory-based learning to practical training through the real immersion of students into the operation of trains, station environments, and emergency scenarios. EduRail is designed per the TRES-D methodology; thus, it offers dynamism and interactivity during learning, with framing targeted to meet university needs and professional licensed training. The target user for the application are students studying railway related field. In this case, the Faculty of Engineering Technology Students that are currently studying in Universiti Tun Hussein Onn Malaysia (UTHM). The results of user acceptance of this application were evaluated using the System Usability Scale (SUS) method which showed an excellent average score of 84.41.